Lidocaine and Monoethylglycinexylidide Serum Determinations to Analyze Liver Function of Cirrhotic Patients After Oral Administration - Munoz, Alberto E.; Miguez, Carlos; Rubio, Modesto; Bartellini, Maria; Levi, Diana; Podesta, Ana; Niselman, Viviana; Terg, Ruben (Digestive diseases and sciences, 1999)
Our aim was to compare standard liver function tests (serum bilirubin, serum albumin and prothrombin concentration), with lidocaine and monoethylglycinexylidide pharmacokinetic parameters, after oral lidocaine administration, to assess hepatic function of cirrhotic individuals. Twenty-one consecutive cirrhotic patients, nine consecutive acute hepatitis patients, and nine healthy individuals received oral lidocaine. Lidocaine and monoethylglycinexylidide serum concentrations were determined by the TDx system. Cirrhotic patients had higher lidocaine and lower monoethylglycinexylidide serum concentrations and differences in its pharmacokinetic variables, compared to control and hepatitis groups (P < 0.05). Sensitivity of lidocaine serum determinations (100%) was greater than sensitivity of serum bilirubin (57%), serum albumin (62%), and prothrombin concentrations (43%) and monoethylglycinexylidide serum concentrations (57%) in differentiating cirrhotic individuals from controls. In conclusion, after oral administration, lidocaine and monoethylglycinexylidide pharmacokinetic parameters are significantly altered in cirrhotic patients compared to normal and acute hepatitis subjects. Lidocaine pharmacokinetic parameters would be better than those of monoethylglycinexylidide and standard liver function tests in the evaluation of liver function of cirrhotic patients.